International Trade Costs and Trade Flows: Evidence from the West African Monetary Zone (WAMZ) - Ozekhome, Hassan (Finance & Economics Review, 2020)
Purpose: The study examines the effect of international trade costs on trade flows in the West African Monetary Zone (WAMZ), a sub-regional economic bloc within the Economic Community of West African States (ECOWAS). Method: Six member countries of the WAMZ, based on data availability, are examined using panel data estimation technique and the Fully Modified Ordinary Least squares (FMOLS), which is employed to test for the robustness of results, for the sample period of 2006-2018. Results: The study finds a negative and significant effect of international trade costs on trade flows in the WAMZ sub-region. Time to trade is also found to be negatively and significantly related to trade. Exchange rate, financial development (measured by commercial banks’ credit to the private sector), and real GDP growth rate (a measure of growth in annual national income/economic size) have a positive and significant impact on trade in the sub-region. The study further finds evidence that the ease of doing business is positively related to trade in the sub-region, but the impact is weak. Implications: In the light of the empirical findings, the study recommends that policy measures and strategies to reduce international trade costs and time to trade through simplified and harmonized trade procedures be implemented in the sub-region. Policies to encourage national income growth, rapid development of the financial sector and improved ease of doing business should also be implemented in the zone. These should be supported with sound and stable macroeconomic exchange rate management policies, in order to enhance trade and integration in the sub-region.